Magi. 7 : the labyrinth of magic - Otaka, Shinobu (VIZ Media, 2014)
"Balbadd is in the throes of upheaval as Alibaba and the Fog Troop confront the corrupt ruler, Ahbmad. With agents of the Kou Empire waiting to pounce, Alibaba, Aladdin and Sinbad form an alliance to take on the powerful enemies arrayed against them. With Alibaba's newfound Djinn Equip ability and the Sword of Amon, he has the strength, but does he have the will? And will an old friend become his worst enemy?" --